Is less more? Impact of different ablation protocols on periprocedural complications in second-generation cryoballoon based pulmonary vein isolation. Issue 9 (24th July 2017) - Rottner, Laura; Fink, Thomas; Heeger, Christian-Hendrik; Schlüter, Michael; Goldmann, Britta; Lemes, Christine; Maurer, Tilman; Reißmann, Bruno; Rexha, Enida; Riedl, Johannes; Santoro, Francesco; Wohlmuth, Peter; et al.
Abstract: Aims: Second-generation cryoballoon (CB2) based pulmonary vein isolation (PVI) has emerged as an effective treatment option for symptomatic atrial fibrillation (AF). The current study sought to assess the impact of different ablation protocols on the incidence and characteristics of procedural complications in a large patient cohort. Methods and results: A total of 563 consecutive patients with symptomatic AF who underwent CB2-based ablation between July 2012 and January 2016, were assessed. Three different ablation protocols were applied and characterized by (#1) a bonus-freeze following PVI, (#2) no bonus-freeze after PVI, and (#3) a 'time-to-effect'-guided strategy. Major complications occurred in 30/563 patients (5.3%) with phrenic nerve palsy (PNP) as the most frequent complication occurring in 2.7% of the cases. The overall incidence of complications was significantly lower in patients treated with a 'time-to-effect' guided ablation strategy compared with the other ablation protocols (8.1% [17/211] (protocol #1+#2) vs. 3.7% [13/352] (protocol #3), respectively; P  = 0.026). The 'time-to-effect' guided ablation protocol was associated with less applied freeze-cycles and shorter freeze-cycle durations. Additionally, shorter procedure times, radiation exposures and lower volumes of contrast medium needed were assessed for the 'time-to-effect' guided protocol as compared with the other ablation protocols. Conclusion: The overall incidence of complications was 5.3% in our analysis. The most frequent complication was PNP. The use of a time-to-effect guided ablation protocol was associated with a lower incidence of major complications compared with a bonus-freeze and no bonus-freeze protocol.